(untitled) (Revista Sistemas de Producción Agroecológicos, 2013)
Were characterized eleven accessions of hot chili under Universidad de Los Llanos environment condition, located twelve km road to Puerto Lopez. The genotypes were sowing in black plastic bags (15 x 15 x 50 cm) under artificial shade. Sixteen plants per genotype were evaluated at flowering and fruiting set stage, using IPGRI methodology. The flowering and tillering stage start at the same time, with one or two flowers per axil and the flower remains open during fifteen days. The fruit set of Jalapeño, Pajarito and Cayene, were at 81,102 and 103 days after sowing, respectively. However, the genotypes Conito and Yacaré, the fruit formation was at 129 and 134 days.